Frequency of Nutritional Rickets in Children and Association with Iron Deficiency Anemia - SUMAYYA AFTAB, IQRA WAHEED, IFTIKHAR EJAZ, AMNA AHMED, (Journal of Fatima Jinnah Medical University, 2018)
Background: Nutritional rickets is a prevalent problem in developing countries. Despite extensive research the exact prevalence in Pakistan could not be found. Vitamin D deficiency is widespread throughout the world and is associated with rickets in children and iron deficiency anemia (IDA). Objectives: Objectives of this study were to determine the frequency of nutritional rickets in children aged 6months to 5years and to determine the frequency of IDA in children with nutritional rickets. Materials and Methods: This cross sectional study was conducted in the Children’s Hospital, Lahore for 6 months. 300 children were included in the study through non probability purposive sampling technique. Informed consent and demographic information of child were taken from parents / guardian. Biochemical profile , x-ray wrist , hemoglobin, MCV and ferritin levels were done to assess rickets. Results: Mean age was 25.16±17.84months. There were 110 (36.7%) children of <1yr age, 123 (41.0%) had age between 1-3yrs and 67 (22.3%) had age between 3-5yrs. There were 145 (48.3%) male and165 (51.7%) female children. The frequency of nutritional rickets in a sample size of 300 children was 44(14.7%). Out of 44 children with nutritional rickets, 21(47.7%) had concomitant IDA. Conclusion: Nutritional rickets is a very common problem in our country and the cases that were found in this study represent a small percentage as a huge number of subclinical rickets is prevalent in our society and this number merely represents the tip of iceberg.